AN ANALYSIS OF METAPHOR IN ONE DIRECTION ALBUM - Agustin, Tuti Dwi; Tanduklangi, Amri; Sapan, Yulius Tandi (Journal of Teaching English, 2019)
Lyrics in song are intended to send a message to the audience ormusic lovers. Composers use figurative language as the media toconvey their message. One of the figurative languages that is mostlyused in song’s lyrics is Metaphor. This study was intended toinvestigate the types of metaphor used in One Direction Album. Theobjective of this study to identify the types of metaphor found in thesong lyrics and to analyze metaphor meaning in One Direction song.This study adopted a descriptive qualitative research design. Threesongs by One Direction had been chosen as the data of this study;Story of My Life, Steal My Girl and Drag Me Down. The data wereanalyzed its metaphor by using Lakoff and Johnson theory, while ininvestigating the meaning, Chaer’s theory of contextual meaningwas used. The result of the study showed that based on the threetypes of metaphor, structural metaphor becomes the most frequentlyused in the song lyrics, meanwhile 2 of 3 songs used all of the threetypes of metaphor; Orientation, Structural and OntologicalMetaphor. In answering the second research question about themeaning of each metaphor, each lyric has been analyzed throughcontent analysis to know the true meaning of what the song writerwant to express in his/her lyrics and each lyric has differentcontextual meaning which is elaborated further in this study.1Keywords: Metaphor, Meaning, One Direction’s Album